Approaching the intrinsic photoluminescence linewidth in transition metal dichalcogenide monolayers - Ajayi, Obafunso A; Ardelean, Jenny V; Shepard, Gabriella D; Wang, Jue; Antony, Abhinandan; Taniguchi, Takeshi; Watanabe, Kenji; Heinz, Tony F; Strauf, Stefan; Zhu, X-Y; Hone, James C (2d materials, 2017)
Excitonic states in monolayer transition metal dichalcogenides (TMDCs) have been the subject of extensive recent interest. Their intrinsic properties can, however, be obscured due to the influence of inhomogeneity in the external environment. Here we report methods for fabricating high quality TMDC monolayers with narrow photoluminescence (PL) linewidth approaching the intrinsic limit. We find that encapsulation in hexagonal boron nitride (h-BN) sharply reduces the PL linewidth, and that passivation of the oxide substrate by an alkyl monolayer further decreases the linewidth and also minimizes the charged exciton (trion) peak. The combination of these sample preparation methods results in much reduced spatial variation in the PL emission, with a full-width-at-half-maximum as low as 1.7 meV. Analysis of the PL line shape yields a homogeneous width of 1.43  ±  0.08 meV and inhomogeneous broadening of 1.1  ±  0.3 meV.